STRATEGIC MANAGEMENT OF MADRASAH PRINCIPALS IN IMPROVING INSTITUTIONAL MANAGEMENT QUALITY - Rosyidi, Moch. Imron; Suyanto, Suyanto; Wahyudi, M. Furqon (SYNTIFIC, 2025)
Background. Improving the quality of education in madrasahs greatly depends on the leadership style adopted by the principal. The principal plays a central role in shaping and directing the organizational culture, as well as in empowering and enhancing teacher performance. Research Purpose. This study aimed to describe and analyze the strategic management implemented by madrasah principals to improve the quality of human resources (HR), infrastructure, and finance. ResearchMethod. This research adopts a qualitative approach using a case study method. Data collection techniques include observation, in-depth interviews, and documentation. Multisite Study at Madrasah Aliyah Al Rosyid Ngumpakdalem Dander Bojonegoro and Madrasah Aliyah Al Munawwar Kunci Dander Bojonegoro. Findings. The findings reveal that the principals apply strategic management through three main stages: strategy formulation, implementation, and evaluation. During formulation, the principals develop the vision, mission, and development programs. Implementation includes HR development through training and coaching, infrastructure management through inventory and maintenance, and financial management based on transparency and optimal funding sources. Evaluation is conducted periodically to ensure continuous improvement. Conclusion. The principals play a central role in driving effective and sustainable strategic management, directly impacting the quality improvement of the institutions.